Higher colorectal tissue HIV infectivity in cisgender women compared with MSM before and during oral preexposure prophylaxis. (1st August 2021) - Sekabira, Rogers; McGowan, Ian; Yuhas, Krista; Brand, Rhonda M.; Marzinke, Mark A.; Manabe, Yukari C.; Frank, Ian; Eron, Joseph; Landovitz, Raphael J.; Anton, Peter; Cranston, Ross D.; Anderson, Peter; et al.
Abstract : Objective: The objective of this study was to compare HIV-negative cisgender women (CGW) with MSM for mucosal tissue differences in pharmacokinetics, HIV infectivity and cell phenotype. Design: A substudy of HPTN 069/ACTG A5305, 48-week study of three oral candidate preexposure prophylaxis regimens: maraviroc, maraviroc/emtricitabine and maraviroc/tenofovir disoproxil fumarate (TDF) compared with a TDF/emtricitabine control group. Methods: Plasma, peripheral blood mononuclear cells and cervical and colorectal tissue biopsies were collected at Baseline (no drug), Week 24 and 48 (on drug), and Week 49 (1-week postdrug). Drug concentrations were assessed in all matrices. HIV infectivity was assessed using tissue biopsy 'explants' challenged with HIV ex vivo followed by HIV p24 measurement. Flow cytometry evaluated colorectal cell phenotype. Results: Thirty-seven CGW and 54 MSM participated. CGW's colorectal explant p24 was higher than MSM before (0.31 log10, P = 0.046), during (1.01-1.19 log10, P = 0.016) and one week after (0.61 log10, P = 0.011) study drug dosing. Pooling regimens, cervical explant p24 did not differ among visits. CGW had higher plasma maraviroc and colorectal tissue tenofovir diphosphate and lower colorectal tissue emtricitabine (all P < 0.005) compared with MSM. Each study drug's cervical tissue concentrations were more than 10-fold below paired colorectal concentrations ( P < 0.001). Cell phenotype sex differences included 4% higher CD38+/CD8+ cells at baseline and 3–7% higher CD69+/CD8+ cells throughout Weeks 24–49 in CGW compared with MSM ( P < 0.05). Conclusion: Colorectal explants in CGW demonstrated greater HIV infectivity than MSM with and without study drugs. Small differences in adherence, drug concentration and colorectal tissue flow cytometry cannot fully explain this difference. Abstract : Supplemental Digital Content is available in the text